Observation of second flexural mode enhancement in graphene resonators. Issue 13 (3rd June 2015) - Chen, T.; Mastropaolo, E.; Bunting, A.; Cheung, R.
Abstract : The enhancement of the second flexural mode in a monolayer graphene resonator by an inhomogeneous electrostatic actuation force has been observed. The devices have been fabricated by transferring the graphene onto a poly‐Si/SiO2 /Si substrate whereby the poly‐Si has been released to produce graphene resonators. Enhancement of the second harmonic has been demonstrated by varying the actuation voltage, achieving an amplitude enhancement of up to 95% of the fundamental mode. The reported findings open new perspectives for graphene resonant sensors with enhanced sensitivity.